Detection of Human papillomavirus in surface epithelial ovarian carcinoma using in situ hybridization technique - Alizi, Sana'a M. H.; Mukhlis, Faiza A.; Abdul-Majeed, Ban A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: The role of Human papillomaviruses (HPV) in the etiology of ovarian cancer remains unclear and the results are controversial. Several studies have verified the presence of HPV DNA in both malignant and benign ovarian tumors.Objectives: Determine the percentage of detection of HPV high (16&18) and low risk types (6&11) in surface epithelial ovarian carcinoma compared to benign and control groups.Materials And Methods: Molecular detection and genotyping of HPV DNA were performed in 76 ovarian tissue blocks by using in situ hybridization (ISH) technique for detecting and localization of high risk HPV (16 and 18) and low risk HPV (6&11) types.Results: The presence of ISH signals for HPV DNA in benign group (71%) was higher than that found in malignant group (64%). HPV 16 was the most predominant type followed by HPV18, 6, and 11 respectively in both malignant and benign groups. High risk HPV were presented with low score and high intensity in both malignant and benign tumors. Low risk HPV types were detected in high score and intensity in benign tumors which significantly differed from that with malignant tumors, which revealed low score and low intensity. The percentage of co-infection of low risk HPV6&11 in benign group was higher (16.9%) than malignant group (7.1%). Only significant difference was found in combination of both high and low risk HPV types.Conclusions: This finding reflects a possible role of HPV virus in the carcinogenesis of ovarian tumors. HPV infection may play a relative role in the pathogenesis of ovarian carcinomas or it could facilitate its progression.